Needham Model Based Instructional Multimedia Material for Teaching Digital Logic Gates - Lee, Ming Foong; Mat Yusoff, Siti Nursaadah; Tan, King Hyiang; Lim, & Johnson Soon Chong (Journal of Technical Education and Training, 2019)
The purpose of this study was to design and develop an instructional multimedia for digital logics gate topic in Electrical and Electronic subject. This topic was chosen as the content-wise of this instructional media due to the teachersâ€™ recommendation. Teachers stated that students are facing difficulty to identify types, symbols, functions and completing the truth tables for logic gate. The failure of students to master this basic concept led them facing difficulty to solve problems involving combinational logic gate, which required students’ skills to build equations, draw logic circuits and complete the truth table in order to get the circuit output. This instructional media was developed using constructivist theory approach, namely Needham Model. This model consists of five phases: orientation, generation of idea, restructuring of idea, application of idea, and reflection. Meanwhile, Three Product Development Life Cycle (PDLC) Phases (Design, Develop, and Review) was used as the research methodology for this study. This instructional media was developed using Microsoft Office Power Point 2007, Adobe Photoshop CS3, Photoscape and Edius 4. This study was divided into three main phases, namely (I) Need Analysis Phase, (II) Development of Instructional Media Phase, and (III) Instructional Media Evaluation Phase. At the Phase I, the user requirements for the instructional multimedia was identified for the purpose to design. Based on the findings at Phase I, the instructional media was developed at Phase II. At Phase III, the developed instructional multimedia was evaluated through the expertsâ€™ validation and review from the aspect of pedagogy, engineering content-wise, and the multimedia elements. The findings showed that expertsâ€™ feedback and comments for the instructional multimedia was positive. As a conclusion, teachers were encourages to use instructional multimedia based on Needham Model to enhance student performance in logic gate topic.